INFLUENCE OF SERVICES AND FACILITIES ON GUEST SATISFACTION ON ANTARES HOTEL - Indri Elysa Putri; Edi Winata (Jurnal Ekonomi, 2023)
This study discusses customer satisfaction. This is based on short interviews conducted with guests staying at the Antares Hotel. This study shows an indication of visitor dissatisfaction with the facilities and quality of services provided. These problems are based on short interview observations addressed to overnight guests. Visitors are not pleased with the facilities or the caliber of services offered. Customers who booked accommodation reported that they were not what they expected. There are several comments in the facilities section about the toilet in the room which is smelly and dirty, the sheets and pillows are stained, the air conditioner is not cold enough, and some rooms of the same type don't have a coffee maker, which makes guests feel disappointed and dissatisfied, indicated as lack. The main objective of this study is to determine whether the quality of facilities (X1) and service (X2) affects customer satisfaction (Y). Multiple linear regression models are used in the quantitative descriptive technique of this study as a data analysis tool. The survey was sent to 87 visitors and analyzed using SPSS software. evaluate the research hypothesis using the R2 test, t-test, and f-test. The results of this study indicate that the level of customer satisfaction is influenced by the quality of facilities and excellent service. According to the partial test findings, it was also found that facilities and customer satisfaction have a positive relationship, but there is no relationship between service quality and customer happiness, which is proven by a negative count. While there is evidence that the quality of facilities and services has an impact of 44% on customer satisfaction